Kinetic study of copper (II) ions removal by axonopus compressus - Choo, Yee Ching (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Investigation of Axonopus compressus as a potential low-cost bio-adsorbents to remove Copper (II) ions from aqueous solution in a batch system. Kinetic and isotherm studies were carried out by studying the effect of parameters such as contact time, initial concentration of Cu2+ ions, pH, and adsorbent dosage. The surface texture of before and after adsorption were observed using Field Emission Scanning Electron Microscope (FESEM). Rough and uneven surface from FESEM image showing properties of bio-adsorbents needed to provide adsorption sites for binding. The adsorption process is rapid in the first 15 minutes and then kept constant. Parameter study showed the optimum pH for the adsorption process was found to be pH 5.8. The adsorption isotherm and kinetics modelling of adsorption can be presented by Freundlich isotherm and pseudo-second-order model respectively. The maximum adsorption capacity was 6.06 mg of Cu2+ ions per gram of A. compressus bio-adsorbent. A. compressus was able to adsorbed Cu2+ ions in wastewater even the concentrations is 0.0865 mg/L which is extremely low.